2015
DOI: 10.1159/000369888
|View full text |Cite
|
Sign up to set email alerts
|

From Theory to Clinical Practice: A Phenomenologically Inspired Intervention for Patients with Schizophrenia

Abstract: Background: Phenomenological conceptualizations of schizophrenia regard the fundamental transformation of self-experience as the central feature of the schizophrenic state of mind. Recently, self-disorders as subtle, trait-like, merely subjective alterations of self-experience have received vast empirical attention. However, the question of how to address self-disorders psychotherapeutically has remained neglected. Methods: From phenomenologically inspired analyses of self-disorders we derive a therapeutic int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
1
1
0
1
Order By: Relevance
“…These authors suggest that, “The patient experiences his I, self, or person as being divided or otherwise compartmentalized, disintegrated into semi-independent parts, or not existing as one unified whole” (p. 248). They also identify “bodily disintegration” as well as “demarcation/transitivism” disorders which involve, invoking language consistent with psychoanalysis, a “loss of permeability of self-world boundary.” Consistent with this, other phenomenologists have observed that, “The integrated and holistic organization of perceptions and habitualized motor patterns may fall apart into unrelated fragments” (Nischk, Nischk, Rusch, & Merz, 2015).…”
Section: Historical Survey Of the Concept Of Fragmentationsupporting
confidence: 56%
See 1 more Smart Citation
“…These authors suggest that, “The patient experiences his I, self, or person as being divided or otherwise compartmentalized, disintegrated into semi-independent parts, or not existing as one unified whole” (p. 248). They also identify “bodily disintegration” as well as “demarcation/transitivism” disorders which involve, invoking language consistent with psychoanalysis, a “loss of permeability of self-world boundary.” Consistent with this, other phenomenologists have observed that, “The integrated and holistic organization of perceptions and habitualized motor patterns may fall apart into unrelated fragments” (Nischk, Nischk, Rusch, & Merz, 2015).…”
Section: Historical Survey Of the Concept Of Fragmentationsupporting
confidence: 56%
“…They also identify "bodily disintegration" as well as "demarcation/transitivism" disorders which involve, invoking language consistent with psychoanalysis, a "loss of permeability of selfworld boundary." Consistent with this, other phenomenologists have observed that, "The integrated and holistic organization of perceptions and habitualized motor patterns may fall apart into unrelated fragments" (Nischk, Nischk, Rusch, & Merz, 2015).…”
Section: Fragmentation In Phenomenological and Existential Modelsmentioning
confidence: 54%
“…Wir nehmen deshalb an, dass Versprachlichung und Konzeptualisierung helfen können, die innere Dialogfähigkeit wieder in Gang zu bringen, um ein vorläufiges Verständnis der psychotischen Erfahrungen zu entwickeln. Um dies zu überprüfen, führten wir eine kleine kontrollierte Studie an 32 Patienten mit (sub-)akuten Störun-gen aus dem schizophrenen Spektrum durch (19), die jedoch aufgrund ihrer klinischen Zielsetzungen auf einer konventionellen Akutstation durchgeführt wurde. Die Experimentalgruppe (EG) erhielt an fünf aufeinander folgenden Tagen eine Kurzintervention (10)(11)(12)(13)(14)(15), in der ein vorher miteinander festgelegtes Zielsymptom anhand eines formalisierten Vorgehens gemeinsam versprachlicht und anschließend konzeptualisiert wurde.…”
Section: Gemeinsames Versprachlichen Und Konzeptualisierenunclassified